Prevalence of Respiratory Manifestations in Chronic Kidney Diseases; A Descriptive Cross-sectional Study in A Tertiary Care Hospital of Nepal - Pankaj Pant; Santosh Baniya; Ashish Jha (Journal of Nepal Medical Association, 2019)
Introduction: Chronic kidney diseases affect patients with multiple respiratory complications by varied etiopathogenesis adversely affecting the outcome in them. The aim of the study is to find out the respiratory manifestations among patients with chronic kidney disease.